Pengaruh Harga dan Store Atmosphere terhadap Kepuasan Konsumen pada Café Dreamblack Coffee Mojokerto - M. Syamsul Hidayat (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2020)
The culinary businesses increase in the establishment such as cafes in CityMojokerto indicates that the result of market demand for the culinary field which also continues to increase. This study aims to determine the effect of Price and store atmosphere on customer satisfaction at Dream Black Coffee cafe partially and simultaneously. This research is a quantitative approach research. The population in this study is Dream Black Coffee consumers. The sampling technique uses accidental sampling technique and purposive sampling with a total sample of 125 people. Data collection techniques use a questionnaires, observation and documentation. The data analysis technique used is the classical assumption test analysis and multiple linear regression. The results show that Price and store atmosphere have a positive and significant effect on customer satisfaction in Dream Black Coffee partially, this is seen from the significant value 0.000 smaller than 0.05 with a value of t count 3.831 and a positive regression coefficient of 0.221, while the price shows a significant value of 0.000 smaller than 0.05 with a calculated value of 9,801 and a positive regression coefficient of 0.356. While simultaneously obtained the calculated F value of 53,441 with a significance value of 0.000 less than 0.05 so that it is concluded that price and store atmosphere simultaneously have a positive and significant effect on customer satisfaction.